2006
DOI: 10.1007/s00259-005-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3′-deoxy-3′-[18F]fluorothymidine PET to monitor early responses to radiation therapy in murine SCCVII tumors

Abstract: Our finding that tumor uptake of FLT was reduced at 24 h after radiation treatment suggests that FLT PET may be a promising imaging modality for monitoring the early effects of radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 35 publications
8
44
0
1
Order By: Relevance
“…Importantly, these reductions in FLT tumor uptake were not secondary to decreases in tumor volume, because early reduction in FLT uptake occurred during the first few days of cytostatic tumor growth. Similar findings were reported in other FLT-PET preclinical studies that used different anticancer therapies, including chemotherapy (15,16,19) and radiation (12,17). Our data lend further support to the literature showing the ability of FLT-PET to detect therapeutic alterations in tumor biology before changes in tumor size are clinically detectable.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, these reductions in FLT tumor uptake were not secondary to decreases in tumor volume, because early reduction in FLT uptake occurred during the first few days of cytostatic tumor growth. Similar findings were reported in other FLT-PET preclinical studies that used different anticancer therapies, including chemotherapy (15,16,19) and radiation (12,17). Our data lend further support to the literature showing the ability of FLT-PET to detect therapeutic alterations in tumor biology before changes in tumor size are clinically detectable.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, we showed early decreases in FLT tumor uptake that were more pronounced and specific for tumor proliferation than those of FDG. Furthermore, when normalizing FLT uptake to background (muscle) uptake as was done in other studies (12,18,19), FLT displayed a much greater T/M signal contrast than FDG. Our data provide additional evidence for the assertion that imaging tumor proliferation with [ 18 F]FLT is more suitable for monitoring treatment response than imaging tumor glucose metabolism.…”
Section: H]flt and [mentioning
confidence: 89%
“…PET is currently relied on as a noninvasive technique for the detection of early-phase responses of tumor cells to therapy (e.g., chemotherapy and radiotherapy) (4,(13)(14)(15)(16)(17). L-11 C-MET and 18 F-FLT imaging has been reported to show more sensitivity and faster response to irradiation than does 18 F-FDG imaging (4,(13)(14)(15).…”
mentioning
confidence: 99%
“…The potential of 18 F-FLT PET/CT for early assessment of chemotherapy has been demonstrated in a variety of cancers (101)(102)(103). In the context of radiotherapy, 18 F-FLT PET/CT first proved its sensitivity to ionizing radiation in preclinical tumor models (104,105). After promising results from 18 F-FLT PET/CT-based assessments of radiation response in these models, an increasing number of studies have shown that decreased 18 F-FLT uptake early (as early as 5 d/ 10 Gy) in the course of radiotherapy or chemoradiotherapy is a strong indicator of long-term outcome in a large-animal preclinical model (106) and humans (107)(108)(109)(110) (Fig.…”
Section: Prognostic Role Of Molecular Imaging In Radiation Therapymentioning
confidence: 99%